Analysis of Income and Feasibility of Alcoholic Beverage (Sopi) Management Business in Trana Village, Teon Nila Serua District, Central Maluku Regency - Batfjor, Fransiskus Sergius; Salakory, Melianus; Riry, Roberth Berthy (Jurnal Pendidikan Geografi Unpatti, 2023)
The research was conducted on managing traditional alcoholic beverages (sopi) as a source of income and the feasibility of community businesses. This study uses descriptive research, which describes the phenomena that occur at the research location and then explains them using frequency tables and illustrations. Data collection techniques used are observation, questionnaires, interviews, and documentation. Data analysis techniques are conducted descriptively, and quantitative data is analyzed using frequency tables. Meanwhile, income analysis is calculated using the Break Even Point formula, and business feasibility is assessed using the R/C ratio formula. Based on the research results, the income analysis from processed sopi shows a break-even point from the production results, with excess income compared to the total expenses incurred to obtain that income amounting to Rp. 1,500,000. The feasibility of the Sopi processing business is considered viable, with a calculated result of 2.73 using the formula. This calculation indicates that R/C > 1, meaning that the farming business is feasible to pursue